2021
DOI: 10.3390/insects12070617
|View full text |Cite
|
Sign up to set email alerts
|

Hyperparasitism of Acroclisoides sinicus (Huang and Liao) (Hymenoptera: Pteromalidae) on Two Biological Control Agents of Halyomorpha halys

Abstract: Halyomorpha halys (Stål) is an invasive Asian pest that causes severe crop losses on various crops. Nowadays, management strategies against this pest mainly rely on pesticide use, but biological control with egg parasitoids is considered the most promising long-term and sustainable solution. Trissolcus japonicus (Ashmead) and Trissolcus mitsukurii (Ashmead) are Asian egg parasitoids already present in Europe and are the most effective biological control agents of H. halys. Therefore, these two species are cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Giovannini et al (2021) reared A. sinicus on both T. japonicus and T. mitsukurii, and though not designed to test for host preference, ~ 2.7 times as many A. sinicus were produced under similar conditions on T. mitsukurii than on T. japonicus. Laboratory studies by Mele et al (2021) found > 20:1 preference for T. mitsukurii compared to T. japonicus using a colony of A. sinicus derived from and maintained on T. mitsukurii parasitized BMSB eggs. However, growing evidence indicates that genetic variation in behavior and conditioning during the adult stage in insects can contribute to preference for the host on which the insect developed (Barron 2001).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Giovannini et al (2021) reared A. sinicus on both T. japonicus and T. mitsukurii, and though not designed to test for host preference, ~ 2.7 times as many A. sinicus were produced under similar conditions on T. mitsukurii than on T. japonicus. Laboratory studies by Mele et al (2021) found > 20:1 preference for T. mitsukurii compared to T. japonicus using a colony of A. sinicus derived from and maintained on T. mitsukurii parasitized BMSB eggs. However, growing evidence indicates that genetic variation in behavior and conditioning during the adult stage in insects can contribute to preference for the host on which the insect developed (Barron 2001).…”
Section: Discussionmentioning
confidence: 98%
“…In parasitoid wasps, conditioning during "critical periods" during the adult stage may have a profound impact on host selection behavior (van Emden et al 1996;Bjorksten and Hoffmann 1998;Barron 2001). Hence, the strong laboratory host preferences demonstrated in A. sinicus by Mele et al (2021) may not be applicable to the field where hyperparasitism levels are low (Mele et al 2022). In the model, we assumed equal preference for T. japonicus and T. mitsukurii, but the capacity to incorporate unequal preference is a component.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations